Studying the Thermodynamic Functions of adsorption of ion , Pb (II) on a new composite surface - Isam Hussein Ali (Journal of Wasit for Science and Medicine, 2023)
A new type of compound was prepared in this study (AML). It was infrared spectroscopy. Use the composite to remove the Pb + 2 lead ion from its Aqueous solution by adsorption at certain conditions of the temperature and weight of theadsorbent material and the acidity and contact time. The composite was found to be effective in removing the lead ion at an acid function higher than 7 and at 25 ° C and contact time (90 min. The results showed that the adsorption on the surface was followed by Freundlich for adsorption. The thermodynamic functions (ΔS°,ΔH°,ΔG°) were calculated